Scholarly solutions: the development of American political science from the Gilded Age to the Great Society - Hotson, L (2017)
This thesis describes the development of the discipline of Political Science in the United States between the so-called ‘Gilded Age’ of the late nineteenth century and the heyday of expertise ushered in by the ‘Great Society’ programmes of the 1960s. It assumes a novel approach to the history of American Political Science by focusing on the interface between the discipline and society. This marks a break from, on the one hand, ‘internal’ disciplinary histories which pay scant attention to the broader social and political environment in which the discipline of Political Science was situated and, on the other hand, historical surveys that give only limited attention to the intellectual concerns and preoccupations of its practitioners. As a discipline oriented to the challenges of an expanding government in a nation that – despite a massive growth of government during the twentieth century – has been characterised by suspicions of both centralization and of ‘experts’, the development of the discipline was never unproblematic. But this thesis describes how leading proponents of the discipline have responded to these challenges and established the study of American politics within the American academy. It argues that the first generation of American political scientists were stimulated into existence by the rapid maturation of American government and politics at the end of nineteenth century, and subsequent generations were animated by its ongoing growth and rapid development during the twentieth. The development of the discipline was also shaped by the rising lot of the ‘expert’ in American life more generally – although their claims never went unchallenged. In describing the past of American Political Science, this thesis illuminates broader trends relating to the growth of American government in the twentieth century, the rise of experts in American society and a peculiar dilemma of our own time: as American political scientists find it harder to think of the ‘big picture’ of American politics today.